HUBUNGAN PENGETAHUAN DAN PERILAKU PENCEGAHAN KEPUTIHAN PADA REMAJA KARANG TARUNA DI KABUPATEN CILACAP - Dewi Elliana; Sri Mularsih (Midwifery Care Journal, 2020)
One of the symptoms and signs of disease in female reproductive organs is vaginal discharge. Wrong personal hygiene behavior can cause itching in the vulva, vaginal discharge to an unpleasant odor in the female area. Teenagers are indeed a large group, vulnerable and at risk of reproductive health problems. The purpose of this study was to analyze the relationship between knowledge about personal hygiene with the behavior of preventing whiteness vaginal discharge in young women in Karang Taruna RW 2, Hamlet Village, Cipari District, Cilacap Regency. This study used a cross sectional design. The population is teenage girls aged 16-18 years as many as 30 people. The study use total sampling technique. Result of this study was most respondents were 16 years old (57.1%), Most of the personal hygiene knowledge is sufficient 11 respondents (36.7%), most of the positive behavior of young women in preventing vaginal discharge is 29 respondents (96,7%). There is a significant relationship between the knowledge of personal hygiene with the behavior of prevention of whiteness vaginal discharge (p value 0.01). It means there is a relationship between the two variables. Suggestions in this study is the female teenagers is expected to increase the provision of information on personal hygiene and vaginal discharge prevention for young women and the community